Предмет: Алгебра,
автор: ВаняСеров0707
Помогите решить 4 и 3
Приложения:
Ответы
Автор ответа:
0
(х+1)³+(х-1)³-2х³=12
х³+3х²+3х+1+х³-3х²+3х-1-2х³=12
6х=13
х=13/6= 2 1/6
(1+у)³+(1-у)³-6у²=3у-1
1+3у+3у²+у³+1-3у+3у²-у³-6у²=3у-1
2=3у-1
3у-1=2
3у=3
у=1
х³+3х²+3х+1+х³-3х²+3х-1-2х³=12
6х=13
х=13/6= 2 1/6
(1+у)³+(1-у)³-6у²=3у-1
1+3у+3у²+у³+1-3у+3у²-у³-6у²=3у-1
2=3у-1
3у-1=2
3у=3
у=1
Похожие вопросы
Предмет: Физика,
автор: kazancevalexialeksej
Предмет: Алгебра,
автор: evgenpaslovskij
Предмет: Литература,
автор: dfwfwdghrth
Предмет: Химия,
автор: sannata01
Предмет: Математика,
автор: 12КАТЕРИНА12